Cellulose nanocrystal: electronically conducting polymer nanocomposites for supercapacitors - Liew, Soon Yee (2012)
This thesis describes the use of cellulose nanocrystals for the fabrication of porous nanocomposites with electronic conducting polymers for electrochemical supercapacitor applications. The exceptional strength and negatively charged surface functionalities on cellulose nanocrystals are utilised in these nanocomposites. The negatively charged surface functionalities on cellulose nanocrystals allow their simultaneous incorporation into electropolymerised, positively charged conducting polymer for charge balancing, i.e. co-electrodeposition occurs. The exception is the case of polyaniline-cellulose nanocomposites which formed with uncharged cellulose nanocrystals. As a result, the cellulose nanocrystals form the structural backbone of the nanocomposites in which the mechanical integrity of the nanocomposites becomes significantly improved. In Chapter 1, supercapacitors and the electrode materials are introduced. The equations relating to the characterisation of supercapacitor materials and devices are also introduced in Chapter 1. In the first half of Chapter 2, the basics of electrochemistry and electrochemical methods used in this work are discussed. In the second half, the preparation of the cellulose nanocrystals is reported. Chapters 3 and 4 report the fabrication and characterisation of polypyrrole-cellulose nanocrystal composites with respect to their capacitance, stability and charging characteristics. Chapter 5 discusses the making of the polypyrrole-cellulose nanocomposites at a practical scale for supercapacitors, and consequently reports the making and testing of a laboratory prototype supercapacitor. Chapter 6 extends the PPy work to other ECPs by the fabrication and characterisation of polyaniline and poly(3,4-ethylenedioxythiophene) nanocomposites with cellulose nanocrystals. Finally, Chapter 7 contains the closing conclusions that I have made for this thesis, and in Chapter 8, I have made some suggestions for future work in this area.